Two possible cases of Trichosporon infections in bone-marrow-transplanted children: The first case of T. japonicum isolated from clinical specimens - (:unkn) unknown (My University, 2008)
Trichosporon spp. are emerging as opportunistic agents that cause systemic diseases in immuno-compromised hosts. Trichosporonosis carries a poor prognosis in neutropenic patients. Trichosporon japonicum was isolated from the air and named by Sugita et al. Here we present the first case of T.japonicum isolated from a clinical specimen. Two cases of acute myeloid leukemia who had Trichosporon isolates are discussed because of their rarity and growing importance. T. asahii was isolated from the throat, feces and urine of the first patient. T.japonicum was isolated from the sputum of the second patient. Both cases produced high MICs to itraconazole, and low IMCs to fluconazole and voriconazole. In virulance factor investigations there was (++) biofilm formation in T.japonicum but not in T. asahii. Conventional mycological studies were not adequate for the identification of the isolate at the species level. In our second case as in the first one, the isolate was identified as T. asahii with 99.9% accuracy by API 20C AUX Although two T. asahii isolates from the same patient yielded identical typing profiles by arbitrary primed-MR, the isolates of the two different patients showed different arbitrary primed-PCR typing profiles. However, the genetic identification of the other patient's strain gave the result of T.japonicum.